Investigating Nickel Ferrite (NiFe2O4) Nanoparticles for Magnetic Hyperthermia Applications - Ahmad, Muhammad Naqeeb; Khan, Hamid; Islam, Lubna; Alnasir, M. Hisham; Nisar Ahmad, Shahid; Qureshi, Muhammad Tauseef; Khan, Muhamamd Yaqoob (Journal of Materials and Physical Sciences, 2023)
Many new promising therapeutic and diagnostic methods in medical science use magnetic nanoparticles (MNPs). Drug targeting, tumor detection, and magnetic hyperthermia treatment are the most common fields of interest where already clinical trials are being performed. Nickel ferrite (NiFe2O4) nanoparticles have received much attention for their potential applications in such fields. A series of samples of Nickel ferrite (NiFe2O4) nanoparticles have been synthesized using a co-precipitation route at different annealing temperatures ranging from 150 ? to 1000 ? and labeling them as S1, S2, S3, S4, and S5. The average particle size obtained from XRD data is found to lie in the range of 15 – 55 nm. The crystal structure of the prepared NiFe2O4 four samples annealed at different temperatures is FCC with a lattice constant of 8.34 Å, which agrees with the values. The magnetic properties of the samples were investigated from temperature-dependent hysteresis loops using Vibrating Sample Magnetometer (VSM). The saturation magnetization (coercivity) is found to increase (decrease) with particle size. The hyperthermia measurements are performed by applying alternating magnetic fields of various amplitudes (Oe) and frequencies (kHz). The measured heating ability of the prepared nanoparticles is obtained from the so-called specific absorption rate (SAR), which is found to increase with increasing frequency and field amplitudes. Using the experimentally obtained SAR value, we also used MATLAB code to model the heat diffusion equation to get information on the temperature rise within the tumor as a function of tumor radius and treatment time.The sample S4 annealed at a temperature of 900 ? is found to be the most suitable candidate for hyperthermia applications at the frequency of 543 kHz because of its capability to produce heat in the therapeutic range of 42-48 ? and with an SAR value of 500 W/g.